A Lively Bit of the Front: A Tale of the New Zealand Rifles on the Western Front - Westerman, Percy F. (Percy Francis), 1876-1959; Paget, Walter, 1863-1935 (Salt Lake City, UT : Project Gutenberg, 2012)
"A Lively Bit of the Front" by Percy F. Westerman is a historical novel written in the early 20th century. The story follows a young New Zealander named Malcolm Carr, who is determined to join the fight in World War I after receiving news that his brother, Peter, has been reported wounded and missing on the front lines. The novel captures both the spirit of camaraderie and the realities of war as Malcolm and his friend Dick Selwyn prepare for their enlistment into the New Zealand Rifles. At the start of the narrative, we meet Malcolm Carr, a seventeen-year-old with a strong character, as he waits for mail at the Wairakato Camp in New Zealand. His concern escalates upon receiving a letter revealing that his brother has been reported (3z(Bwounded and missing(3y (Bduring combat in France. The story then details his decision to enlist in the military, the conversations with his friend Dick, and glimpses of their lives at the camp, emphasizing Malcolm's determination to take his brother$1 (Bs place and fulfill his duty. The opening chapters set the tone for an adventure filled with bravery, friendship, and the challenges of war that await them as they embark on their journey to the front lines. (This is an automatically generated summary.)s
Release date is 2012-06-24
Produced by R.G.P.M. van Giesen
Keywords: World War, 1914-1918 -- Juvenile fiction; World War, 1914-1918 -- New Zealand -- Juvenile fiction